Advances of Research in Affective Processes in Communication and Collaboration. (September 2015) - Xu, Jie; Montague, Enid; Gratch, Jonathan; Hancock, Peter; Jeon, Myounghoon; Pfaff, Mark S.; Xu, Jie
Affective processes have been an important research area for human factors and ergonomics. Although there is an obvious connection between affect and communication and collaboration, little research has been conducted in the human factors community until recently. In this panel, the panelists will discuss recent advances in affective research in communication and collaboration systems. Theoretical perspectives in human computer interaction, human agent interaction, and teamwork that take affective process into account will be discussed. Methodological issues will also be addressed, such as the measurements of affect, research design, and data analysis methods. Finally the applications of the theories and methods in different systems, such as human robot interaction, healthcare, and multi-tasking teams, will be discussed.